The relationship between a market orientation and financial performance in South African organisations - S. S. Loubser (South African Journal of Business Management, 2000)
Organisations are in constant flux and with powerful universal trends such as globalisation, technological discontinuity, deregulation and new competencies within a continuously changing environment, both business leaders and academics are searching for new insights into organisational dynamics. In recent years more and more academics have suggested that a market orientation should be considered as a business philosophy and/or business behaviour that will lead to better business performance. However, not much research has been done on this organisational phenomenon and it is not well understood. Market orientation has been defined in this study as the business culture that is focused on creating mutually rewarding relationships between customers and the organisation based on a foundation where (I) the interests of all stakeholders are actively pursued: (2) competitive advantage is based on the organisation's ability to learn from the market itself, and to mobilise core competencies in response: (3) a set of beliefs exists that puts the customer's interests first: and (4) processes exist that support this belief. This study differs from previous empirical research on market orientation in that it takes a systemic view of market orientation, rather than a cause-effect view. It considered 449 unlisted and 51 listed organisations, and found that a market orientation leads to better financial results. Also, market orientation is a necessary, but maybe not sufficient, condition for business excellence, and further research needs to be done in this regard.
Keywords: 650